EFEKTIFITAS AROMATERAPI LEMON TERHADAP PENURUNAN INTENSITAS MUAL AKIBAT KEMOTERAPI PADA PASIEN KANKER DI RSUD ARIFIN ACHMAD PEKANBARU - Asni " Martius; Siti " Rahmalia; Rismadefi " Woferst (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
Abstract The purpose of this research was to analyze the effect of lemon aromatherapy on reduction of chemotherapy patient’s nausea frequency in RSUD Arifin Achmad Pekanbaru. This research was Quasy eksperimentalwith one group pra-post test design. The research sample consists of 30 chemotherapy patient who experience nausea which were determined by purposive sampling technique. The measuring instrument in this research was tabels frequency. The data analysis used paired t-test with p value = < 0,05. The result showed that mean of the nausea frequency before giving lemon aromatherapy was 1,27 with standard deviation 0,458 and after giving lemon  aromatherapy is 1,07 with standard deviation 0,961. The difference of mean value was 1,07 with p value=0,001(p<0,05). It means that there are significant effect of lemon aromatherapy on reduction of chemotherapy patient’s nausea frequency in RSUD Arifin Achmad Pekanbaru. Keyword:Cancer, chemotherapy,lemon aromaterapy, nausea,